Propuesta para la creación de una agencia de viajes virtual para el rescate y promoción del patrimonio cultural inmaterial de la ciudad de Otavalo - Hidrobo Arévalo, Cintya Liseth (2021)
Tourist operators generate activities that take advantage of natural and cultural resources, in a sustainable and sustainable way to boost the economy of a given place, it is an opportunity for development both in the economic field as well as in the development of tourism and the use of the natural resources and development of society, taking into account the current reality that are handled around technology, the creation in the Otavalo canton of a virtual tour operator is seen as a proposal\; Through this idea of tourist operation through e commerce, which is the management of commerce through the internet or more commonly called electronic commerce, it is intended in such a way to offer the products and services that the Otavalo canton has to make available to tourists who are traditionally attracted by the culture and origin of its inhabitants thus developing more tourist activities in the canton. This research is based on the collection of bibliographic information related to tourism, electronic commerce, tourist activities in Otavalo among others, taking as a contribution to the generation of this research proposal and knowing, as well as contributing and transfers are the benefits that they are obtained for the canton and also for its population in general. The present research developed research techniques such as surveys and interviews that were applied to authorities and the economically active population that come to do tourism in the Otavalo canton, which resulted in a favorable acceptance of the proposal by a virtual tour operator, with a summary response of the applications of our investigative techniques.